Sexting: A Digital Gateway to Understanding Risk Propensity and Alexithymic Traits - Rajesh, Lakshmi; Pandian, Durga Rangaswamy; Madanagopal, Darshini; Priya M, Nandhini; N, Tharani; Nayana R, Divya (South Eastern European Journal of Public Health, 2024)
Aim: The current study explores the patterns of sexting behaviour among individuals actively using online dating apps, with a focus on whether sexting can predict Alexithymic traits and risk-taking behaviours, while also delving deeper into the relationship between the different variables. Methods: This quantitative study employs convenience sampling to recruit 194 individuals, aged 18-25, who are active users of online dating apps across Chennai. The variables were quantified using standardised measures which include; Sexting Behaviours Scale (SBS), The Risky, Impulsive, & Self-destructive behaviour Questionnaire (RISQ), and Toronto Alexithymia Scale Questionnaire (TAS - 20) . The data obtained were then subject to correlation analyses using SPSS software. Results: The results of the study highlight significant relationships between sexting, alexithymia and risk taking behaviours. Findings show that individuals with high levels of alexithymia are much more likely to partake in sexting and the other array of risk taking behaviours as a form of coping mechanism. These results underscore the role of emotional dysregulation in driving risk - taking tendencies, providing us with valuable insights into the psychological factors influencing the behaviors. Conclusion: The findings of the study delve into the complex relationship between young adults’ risk taking behaviors, alexithymia and sexting behavior, with a focus on the domain of online dating. They contribute to the growing body of literature by emphasizing the psychological and behavioral implications of sexting in the digital age, thereby paving the way for developing targeted interventions to mitigate these risks.